1988
DOI: 10.1128/jb.170.6.2639-2645.1988
|View full text |Cite
|
Sign up to set email alerts
|

Truncated forms of Escherichia coli lactose permease: models for study of biosynthesis and membrane insertion

Abstract: Using in vitro DNA manipulations, we constructed different lacY alleles encoding mutant proteins of the Escherichia coli lactose carrier. With respect to structural models developed for lactose permease, the truncated polypeptides represent model systems containing approximately one, two, four, and five of the N-terminal membrane-spanning a-helices. In addition, a protein carrying a deletion of predicted helices 3 and 4 was obtained. The different proteins were radiolabeled in plasmid-bearing E. coil minicells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
3
12
1
Order By: Relevance
“…The results presented in this communication are consistent with the conclusion that although the N-terminal hydrophobic domain of lac permease may be required for insertion into the membrane (25,26) and is oriented toward the inner surface, it does not determine the topology of the C-terminal Ottemann, T. J. Silhavy, and J. Beckwith, personal communication). Moreover, it has been shown that there are multiple sequences in lac permease that are independently able to support translocation of alkaline phosphatase (C. Manoil, personal communication).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results presented in this communication are consistent with the conclusion that although the N-terminal hydrophobic domain of lac permease may be required for insertion into the membrane (25,26) and is oriented toward the inner surface, it does not determine the topology of the C-terminal Ottemann, T. J. Silhavy, and J. Beckwith, personal communication). Moreover, it has been shown that there are multiple sequences in lac permease that are independently able to support translocation of alkaline phosphatase (C. Manoil, personal communication).…”
Section: Discussionsupporting
confidence: 85%
“…Evidence for the general features of the model and the demonstration that both the N and C termini are on the cytoplasmic surface of the membrane has been obtained from other spectroscopic measurements (13),t chemical modification (14), limited proteolysis (15, 16), and immunological studies (17-23), and strong exclusive support for the 12-helix motif has been obtained from analysis of an extensive series of lacY-phoA (lac permease-alkaline phosphatase) fusions (24). Stochaj and coworkers (25,26) demonstrated that sequences within the first 170 amino acid residues of the lac permease may be important for insertion. Moreover, a truncated permease containing only the N-terminal 50 amino acid residues is inserted into the membrane, and it was proposed that this region contains an internal "start transfer" sequence that results in the insertion of the N terminus as a "helical hairpin" (27,28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…residues of lactose permease were intimately associated with the lipid bilayer (27,28). These data suggested that the N-terminal region exhibits a certain autonomy in interacting with the lipid bilayer.…”
mentioning
confidence: 66%
“…In the case of the E. coli lacY product, biochemical data support a cotranslational mode of integration into the cytoplasmic membrane. Pulse-labeling studies of E. coli cells expressing C-terminally truncated forms of the lactose permease indicate a rapid association of nascent chains with the cytoplasmic membrane (49); N-terminal portions of LacY permease as short as 50 amino acids are able to target nascent chains to the lipid bilayer and mediate apparent attachment of the ribosomes to the membrane during chain elongation (49,50). Studies of the synthesis of lactose permease in an E. coli cell-free transcription-translation system also support a model of cotranslational insertion of the nascent polypeptide into the cytoplasmic membrane.…”
Section: Resultsmentioning
confidence: 99%